Notes on the original materials of the three western Mediterranean oaks (Quercus, Fagaceae) described by Desfontaines - Vila-Viçosa, Carlos Martins; Vieira, Cristiana; Márquez, Francisco; Almeida, Rubim; Vázquez, Francisco María (Mediterranean Botany, 2022)
We examined specimens from René Louiche Desfontaines, deposited in the “Herbier de la Flore Atlantique” (P-Desf) from MNHN-P and homologue specimens from P-Lam, LINN-HS, MPU, FI-Webb, and B-W, to assess three names of western Mediterranean oaks (Quercus L.) that are distributed across across the Iberian Peninsula and North Africa. Specifically, we bring insights to the names Quercus ballota, Q. pseudococcifera., and Q. pseudosuber, after a thorough examination of the original specimens, combined with the analysis of the respective protologues. The results highlight the need for wider and detailed natural history and classic herbaria surveys to promote the discussion and better understanding of species delimitation and biogeographic awareness, especially in crucial groups, that are still involved in taxonomic and evolutionary discussion, as the trees that form the potential climacic forests of the Northern Hemisphere.